Meningkatkan Kemampuan Guru Dalam Melaksanakan Penelitian Tindakan Kelas Melalui Teknik Workshop di SDN 7 Telaga Biru dan SDN 9 Telaga Biru Kabupaten Gorontalo - Tululi, Imran (Universitas PGRI Adi Buana Surabaya, 2019)
The problem examined in this study is whether the ability of teachers to carry out classroom actionresearch in the 7 primary schools of Telaga Biru and the 9 primary schools in Telaga Biru GorontaloRegency can be improved through workshop techniques?